PENGARUH KECEMASAN DAN KUALITAS TERHADAP NIAT KONSUMEN MENGGUNAKAN DENGAN SIKAP SEBAGAI MEDIASI BAGI PENGGUNA PRODUK WARDAH LIGHTENING SERUM AMPOULE DI SURABAYA - Ravika Wulan Ramadhani; Aniek Maschudah Ilfitriah (Jurnal Ilmiah Global Education, 2023)
This research was conducted to obtain empirical evidence of the effect of anxiety on attitudes, quality on attitudes, anxiety on consumer intentions, quality on consumer intentions, and attitudes towards consumer intentions for users of Wardah Lightening Serum Ampoule products in Surabaya. This study uses a quantitative approach. The sampling technique in this study was carried out by non-probability sampling and the sample method used was purposive sampling. The sample in this study were 100 users of the Wardah Lightening Serum Ampoule product in the city of Surabaya. The data processing analysis tool method in this study uses SEM SmartPLS 3.0. The results of this study were H1 was rejected, H2 was accepted, H3 was accepted, H4 was rejected, and H5 was accepted.